UFMC system performance improvement using RS codes for 5G communication system - Ghasan Ali Hussain; Lukman Audah (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
Fifth generation (5G) mobile communication is expected to be deployed in several countries by 2020. Where, the data consumptions are expected to be increased to 30% thus, it cannot be supported by the present technologies 3G and 4G. In contrast, looking for new alternative modulation techniques of orthogonal frequency division modulation (OFDM) system which is suffering from high Peak to Average Power Ratio (PAPR) and out of band (OOB) side lobes are needed to use in 5G communication system. Hence, Universal Filtered Multi-Carrier (UFMC) is considered as alternative waveform to overcome of OFDM disadvantages. In communication systems, channel coding is considered vital part, where error correction codes (ECC) are used to detect and correct the errors which is occurring in channel noise. In this paper, RS codes are suggested with UFMC system to achieve the reliability of information transmission over noisy channels. The results showed that although, the values of PAPR levels for using RS codes in UFMC increased to 8.8653dB against 6.9735 dB for OFDM system. However, there are significant improvements in BER performance owing to use RS codes against uncoded-UFMC system. Furthermore, the values of OOB in UFMC system was lower than OFDM system.